Respostas
respondido por:
0
Resposta:
a27 = 13 >>>>
Explicação passo-a-passo:
a1 = - 13
a2 = -14
a3 =- 15
r = a2 - a1 ou -14 - ( -13 ) ou -14 + 13 = - 1 >>>>
an = a1 + ( n - 1).r
a27 = a1 + ( 27 -1 ).r
a27 = - 13 + 26. ( -1 )
a27 = -13 - 26 .(-1)
a27 = -13 + 26
a27 = + 13 >>>
respondido por:
0
Resposta:
13
Explicação passo-a-passo:
R = a2-a1
R = -14-13 => R=-1
an = a1+(n-1)xR
a27 = a1+26xR
a27 = -13+26x(-1)
a27 = -13+26
a27 = 13
Perguntas similares
5 anos atrás
8 anos atrás
8 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás